Slip kinematics and dynamics during and after the 1995 October 9 Mw = 8.0 Colima–Jalisco earthquake, Mexico, from GPS geodetic constraints - Hutton, W.; DeMets, C.; Sánchez, O.; Suárez, G.; Stock, J. (Geophysical journal international, 2001)
We use horizontal and vertical crustal displacements derived from GPS measurements at 26 sites in western Mexico to study the coseismic and post-seismic kinematics and dynamics of the 1995 October 9 (Mw = 8.0) Colima–Jalisco earthquake along the Middle America Trench. The measurements bracket the entire landward edge of the approximately 150 km long rupture zone and span a 4 yr period for most sites. We solve for the temporal evolution of slip along the subduction interface by inverting GPS displacements for the coseismic and four post-seismic intervals (March 1995–March 1999), subject to the assumption that the crust responds elastically to slip along a shallow-dipping, curved subduction interface. Coseismic rupture of up to 5 m was largely focused above depths of 20 km and was limited to a 120–140 km long segment of the subduction zone. Within one week of the earthquake, post-seismic slip migrated downdip to depths of 16–35 km, where it has since decayed logarithmically. We also find evidence for shallow aseismic slip during 1996 or early 1997 northwest of the coseismic rupture zone and increasingly widespread relocking of shallow regions of the subduction interface after early 1997. The relative lack of afterslip in shallow regions of the subduction interface suggests that the interface lies in the unstable frictional regime and hence is strongly coupled between earthquakes. By 1999, the cumulative slip moment associated with post-seismic slip equaled ∼70 per cent of the coseismic moment, with nearly all of this slip occurring downdip from the coseismic rupture zone. The migration of slip after the earthquake to a deeper and presumably velocity-strengthening area of the subduction interface and the logarithmic decay of afterslip conform to the qualitative and quantitative predictions of a model in which the fault kinematics are prescribed by rate- and state-variable frictional laws. However, misfits to the geodetic displacements exceed the average displacement uncertainties for all epochs, implying one or more of the following: (1) the elastic response is heterogeneous due to slip along unmodelled upper crustal faults or variations in the elastic properties of the crust; (2) other post-seismic mechanisms such as viscoelastic or poroelastic effects contribute to or possibly dominate the post-seismic response; (3) we have underestimated the uncertainties in the GPS displacements.